Learning to prove: enculturation or...? (2009)
Empirical evidence coming from a curriculum innovation experience that we have been implementing in the Universidad Pedagógica Nacional (Colombia), in a plane geometry course for secondary mathematics pre-service teachers, allows us to affirm that learning to prove, more than enculturation into mathematicians¿ practices, is participation in proving activity within the community of mathematical discourse.